Pembentukan Perangkat Kepatuhan Persaingan Usaha sebagai Strategi untuk Meningkatkan Kepatuhan Persaingan Usaha - Nova Angelina Silalahi (Komisi Pengawas Persaingan Usaha, 2022)
Abstrack Conspiracy is one of the activities that often occurs in the government procurement process of goods and services. The occurrence of conspiracy has the potential to cause state losses due to the end user unable to obtain goods/services with competitive prices. KPPU as a quasi-judicial has made Compliance Program Guidelines as one of the instruments in the framework of establishing fair business competition which is a derivative form of Law No. 5/1999. However, KPPU requires a strategy so that the Compliance Program Guidelines can run effectively for business entity. Referring to the Competition Compliance Toolkits compiled by the Association of Southeast Asian Nations (ASEAN), it is necessary to understand the role of KPPU and business entity, increase awareness and inculcate a culture of fair business competition, establish measurable policies and its business processes, conduct training and also self-assessment for the implementation of the Compliance Program Guidelines under KPPU’s supervision. The Indonesian Government also has to reformulate persuasive regulations, so that business entity could voluntarily comply with Law No. 5/1999.